The Composition of the São Brás Copper Hoard in Relation to the Bell Beaker Metallurgy in the South‐western Iberian Peninsula. (14th September 2018) - Valério, P.; Soares, J.; Araújo, M. F.; Alves, L. C.; Tavares da Silva, C.
Abstract : A large ceramic vessel was discovered at São Brás (southern Portugal) containing a metallic hoard from the Chalcolithic/Early Bronze Age period. These weapons and tools were characterized by microanalytical techniques as being composed of copper with varying arsenic contents (2.2 ± 1.6 wt%) and minor amounts of lead, bismuth and iron. The collection shows a clear association between daggers and copper with a higher arsenic content, which can be explained by the high status of these silvery alloys. Finally, the compositional distribution of the hoard was compared with the metallurgy of the Bell Beaker and non–Bell Beaker communities inhabiting the south‐western Iberian Peninsula.